APPLICATION OF VYGOTSKY'S SOCIAL CONSTRUCTIVISM IN LEARNING MARITIME ETHICS TO FORM STUDENTS' SOCIAL RESPONSIBILITY - I Putu Suarsana; Muhammad David; Dedy Kurniadi; Andi Aulia Arikha Setyo; Sariyulis (Jurnal Maritim Malahayati, 2026)
As an archipelagic nation, Indonesia requires professional seafarers who are not only technically competent but also possess a strong sense of ethical and social responsibility. However, maritime ethics instruction in maritime higher education institutions still tends to be normative and does not encourage active value construction. This study aims to analyze the application of Vygotsky's social constructivism approach in maritime ethics instruction and its contribution to the development of students' social responsibility. The study used a qualitative approach with an exploratory case study design at the Malahayati Maritime Polytechnic in Aceh. Data were collected through in-depth interviews, participant observation, and documentation studies with 20 students and 10 lecturers, then analyzed thematically using NVivo. The results indicate that collaborative learning and social interaction foster the construction of reflective and contextual ethical meaning. The lecturers' implementation of scaffolding within the Zone of Proximal Development (ZPD) helped students develop independent ethical thinking and internalize moral values. Furthermore, there was a transformation in students' social responsibility, demonstrated by increased participation in maritime social activities and concern for coastal communities and marine sustainability. These findings confirm that the social constructivism approach is effective in shaping the character and social responsibility of maritime students